Mitigating Professional Interference for Sustainable Growth in the Nigerian Construction Industry: A Comprehensive Review - Nnadi, Ezekiel Ejiofor; Akabudike, Priscilla Oluchi (Journal of Engineering, Technology, and Applied Science (JETAS), 2024)
The Nigerian construction industry is a dynamic sector with various professional roles and rivalries, crucial for economic development and stability. However, professional interference can hinder its sustainable growth and expansion. A multi-faceted approach involving multiple stakeholders, including government bodies, industry associations, professionals, and the public, is needed to create an environment that promotes professionalism, accountability, and quality in the industry. Understanding the implications and consequences of professional interference is crucial for sustainable growth in the Nigerian construction industry. A qualitative research study identified the core roles of NIA, NIQS, and NSE and the causes of professional interference. According to our study, it is recommended that the Federal Republic of Nigeria create regulatory councils for professional organizations in the construction sector to define their boundaries, tasks, and obligations. Stringent regulations and enforcement of laws are necessary to prevent professionals from overlapping roles and responsibilities, to avoid potential repercussions like losing their practice licenses, tarnishing their reputation, and legal consequences under media scrutiny.